PERAN BPK DALAM PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - hasbullah hasbullah (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
Abstract             In Article 23E paragraph (1) of the Constitution of the Republic of Indonesia Year 1945 states that "In order to examine the management and accountability of state finances held an Audit Board that is free and independent." Based on these provisions can be understood that the Supreme Audit Agency (BPK ) is a state agency that is free and independent in the accountability report on the examination of state financial management by the government. President as head of the government in administering the state holds sway over the country's financial management. Power management of state finances is then delegated to the Minister of Finance, Minister / Head of Institution and Local Government is the Governor, Regent / Mayor. The financial management of the country is used as the overall activities of the country's financial management officer in accordance with the position and authority, including planning, implementation, monitoring and accountability. Obligations of governments and other institutions to implement public finance management must be orderly, obedient to laws and regulations, efficient, economic, effective and transparent with regard fairness and propriety. After the planning and implementation of state finances, the next is the role of the CPC in the process of problem identification, analysis, and evalusai conducted independently, objectively and professionally based standards checking, to assess the validity, accuracy, credibility and reliability of information on the management and financial responsibility of the State , Through Law No. 15 Year 2006 regarding the Audit Board, CPC as the state institutions free and independent in examining the management and financial responsibility the state has an important role. In this case the CPC role in improving accountability and achieving good governance at central and local government. In order to support good governance in state administration, public finance management should be organized in a professional, open and responsible in accordance with the basic rules established in Law Examination, Management and Accountability of State Finance. With that goal the establishment of the state of Indonesia as stipulated in paragraph four of the Constitution of the Republic of Indonesia Year 1945 to realize the welfare state (welfare state) will be reached.